Therapeutic Potential of Stem/Progenitor Cells in Human Skeletal Muscle for Cardiovascular Regeneration - Nomura, Tetsuya; Ashihara, Eishi; Tateishi, Kento; Ueyama, Tomomi; Takahashi, Tomosaburo; Yamagishi, Masaaki; Kubo, Toshikazu; Yaku, Hitoshi; Matsubara, Hiroaki; Oh, Hidemasa (Current Stem Cell Research & Therapy, 2007)
Although myoblast transplantation in patients with ischemic heart failure results in a significant improvement of cardiac function, subsequent studies have consistently shown the myotubes formation in the absence of electromechanical coupling with the neighboring host myocardium, accompanied with the short-term release of paracrine effectors from implanted cells. One major pitfall of using myoblasts is that transplanted cells do not differentiate into cardiomyocytes, which may cause the inherent proarrhythmogenic events. Therefore, whether a discrete subpopulation in heterogeneous muscle-cell cultures is responsible for substantial cardiovascular regeneration has yet to be investigated. We describe here the isolation of progenitor cells from human skeletal muscle. These cells proliferated as non-adherent myospheres in suspension and displayed early embryonic factors and mesenchymal cell-like characteristics. Flow cytometric analyses demonstrated that CD56/N-CAM/Leu-19, a neural cell adhesion molecule abundantly present in myoblasts, was absent in myospheres but was expressed in an adherent cell population containing myogenic precursors. Myospherederived progenitor cells (MDPCs) differentiated in culture to produce cardiac, smooth muscle, and endothelial cells. Transplantation of MDPCs into ischemic hearts in NOD/scid mice promoted angiogenesis with substantial cardiovascular regeneration. Our results provide a foundation to further study the cell and biological function of human MDPCs which may have potential therapeutic implications.
Keywords: mesenchymal cells